Peran Pepadi dalam Melestarikan Kesenian Wayang Golek di Kabupaten Karawang Tahun 2020 - Uka Whardhana; Amung Ahmad Syahrir (UIN Sunan Gunung Djati Bandung, 2022)
Wayang is an archipelago culture that has existed for a long time. Its function is as an entertainment media and information for the people of the archipelago. Because wayang are so rich in moral values and philosophical meanings contained in them that wayang was recognized by the world and UNESCO in 2003. Over time, a puppet organization called Pepadi (Persatuan Pedalangan Indonesia). This organization was formed in Jakarta on July 31, 1975. In completing this research the authors used historical research methods and used descriptive analysis research. Pepadi was formed because of the awareness of the people of the archipelago who love Wayang’s art and it is important in preserving it. Wayang golek is a puppet art which is popular in West Java to the point that it is called wayang of the Sundanese people. Karawang is one of the cities in West Java province that has the most Dalang. The presence of Pepadi in enlarging the art of puppetry in the Karawang district is so important because it aims to make the Karawang community to love traditional arts, especially wayang golek, to create a Karawang community that has dignity and dignity. Pepadi Karawang, in its development in Karawang, has been able to lead the Dalang to make brilliant achievements both at the regional and national levels. The constraints experienced by Pepadi are the lack of Nayaga if there is a puppet performance and the lack of people inviting wayang golek in family events because it requires high costs.